Primary Hepatic Neuroendocrine Tumor with Unusual Thyroid Follicular-Like Morphologic Characteristics - Mohd Elmugtaba Ibrahim; Kerolos Abadeer; Qihui (Jim); Aziza Nassar (Hindawi Limited, 2017)
We describe a primary hepatic neuroendocrine tumor of a 57-year-old Thai woman who presented in 2004 with a suspicious mass in the left hepatic lobe. She underwent left hepatectomy for the 10.5-cm mass, called intermediate grade neuroendocrine carcinoma of unknown origin, likely metastatic. The tumor recurred in 2007, then called recurrent primary hepatic neuroendocrine tumor (PHNET), and the patient underwent liver transplant. Because of similarity between the neuroendocrine tumor and a thyroid tumor-specifically, follicular-like characteristics-immunohistochemical stains for thyroglobulin, TTF1, and calcitonin were performed. However, all were negative. All imaging studies revealed no evidence of a primary lesion other than the liver mass. In 2008, the patient's liver transplant failed because of ischemic cholangiopathy, and she underwent a second liver transplant. Seven years later, in 2015, she presented with metastatic neuroendocrine tumor of intermediate grade to the lung, consistent with metastatic PHNET. She underwent left upper-lobe wedge resection to remove the tumor. The patient is alive with no evidence of disease at 13 years after initial diagnosis. This rare variant of PHNET had thyroid-like morphologic characteristics but there is no evidence of primary thyroid tumor or thyroid markers in the primary and recurrent hepatic tumors and lung metastasis.